The Effect of Digital Marketing Activities on Intention to Buy at Shopee (Study on Generation X and Y) - Mahyuzar , Heri; Kholifah, Kholifah (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to examine the effect of digital marketing activities on purchase intentions at Shopee. The sampling method used in this study was purposive sampling with a total sample of 96 people, and the data collection method was a questionnaire. Hypothesis testing using multiple linear regression analysis. The data was processed with the help of the SPSS 24 program. This study shows that content and social media marketing significantly positively affect purchase intentions. Meanwhile, electronic promotion has no significant effect on purchase intention. In addition, content marketing, electronic promotion and social media marketing simultaneously influence purchase intentions.